Hubungan Antara Insomnia Dan Depresi Pada Lanjut Usia DiKecamatan Mergangsan Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Depression in elderly people is a psychogeriatric problem that finding repeatedly and must get special attention. The older age, chronic disease and depression can cause the elderly people get insomnia. Because of that, we need the elderly psychologic management to remitted depression in elderly people that cause insomnia. This research was aimed to observe correlation between insomnia and depression in elderly people at Kecamatan Mergangsan, Yogyakarta, which used Cross Sectional frame. The figure of sample was 61 people. Geriatric Depression Scale and KSPBJ Insomnia Rating Scale was used in this study. Correlation between insomnia and depression was performed with Pearson Product Moment. Tyie statistic correlation method found a significant correlation between insomnia and depression in elderly people at Kecamatan Mergangsan, Yogyakarta. Keywords: depression-insomnia-elderly-psychogeriatric-kecamatan Mergangsan, Yogyakarta